2014
DOI: 10.1089/ten.tea.2013.0319
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Interconnected Pore Architecture in Injectable PolyHIPEs for Bone Tissue Engineering

Abstract: Template polymerization of a high internal phase emulsion (polyHIPE) is a relatively new method to produce tunable high-porosity scaffolds for tissue regeneration. This study focuses on the development of biodegradable injectable polyHIPEs with interconnected porosity that have the potential to fill bone defects and enhance healing. Our laboratory previously fabricated biodegradable polyHIPEs that cure in situ upon injection; however, these scaffolds possessed a closed-pore morphology, which could limit bone i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
95
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 44 publications
(56 reference statements)
0
95
0
2
Order By: Relevance
“…[54][55][56] However, we have previously demonstrated that pore size of these injectable polyHIPEs can be readily tuned by altering the stability of the emulsion (surfactant concentration, aqueous phase volume fraction, fabrication conditions) to achieve pore sizes greater than 100 mm. 7,8 Given that our current studies demonstrate that the surface modification had minimal effect on pore size, we expect to be able to utilize this technique to modify polyHIPE grafts with larger pores for investigation as bone grafts in upcoming in vivo studies.…”
Section: Potential As Injectable Bone Graftsmentioning
confidence: 91%
See 4 more Smart Citations
“…[54][55][56] However, we have previously demonstrated that pore size of these injectable polyHIPEs can be readily tuned by altering the stability of the emulsion (surfactant concentration, aqueous phase volume fraction, fabrication conditions) to achieve pore sizes greater than 100 mm. 7,8 Given that our current studies demonstrate that the surface modification had minimal effect on pore size, we expect to be able to utilize this technique to modify polyHIPE grafts with larger pores for investigation as bone grafts in upcoming in vivo studies.…”
Section: Potential As Injectable Bone Graftsmentioning
confidence: 91%
“…8 Briefly, the diester 1,2 hydroxypropyl fumarate was synthesized by adding propylene oxide dropwise to a solution of fumaric acid and pyridine in 2-butanone (2.3:1.0:0.033 mol) and refluxing at 75°C for 18 h. Residual reagents were removed by distillation, and the product redissolved in dichloromethane before removing acidic byproducts with washing. The diester product was then dried under vacuum before endcapping with methacrylate groups using methacryloyl chloride in the presence of triethylamine.…”
Section: Macromer Synthesis and Purificationmentioning
confidence: 99%
See 3 more Smart Citations